Renal oncocytoma with liver metastasis: a case report with genetic analysis and literature review - Al-kharouf, Issa; Miller, Carmen; Hamza, Ameer; Li, Benyi; Zhang, Da (Frontiers in Medicine, 2025)
Oncocytomas are clinically benign tumors composed of cells with abundant granular eosinophilic cytoplasm due to a high mitochondrial content. While typically non-metastatic, rare cases of metastatic oncocytomas have been documented. This report describes a unique case involving transcriptome analysis to identify genes associated with the oncocytoma signature. A 57-year-old woman presented to the emergency department with COVID-19 pneumonia. Incidentally, a CT chest scan revealed a large mass in the left upper quadrant. Further imaging of the abdomen and pelvis identified a 14 cm left renal mass and multiple low-density hepatic lesions. A liver biopsy confirmed a PAX-8 and CD10 positive carcinoma, consistent with metastatic renal cell carcinoma. Following neoadjuvant therapy, the patient underwent a left radical nephrectomy, partial hepatectomy, and cholecystectomy. This case emphasizes the rarity of metastatic oncocytoma and the importance of genomic testing in elucidating its molecular underpinnings. By identifying specific genetic alterations linked to the oncocytoma signature, genomic analysis offers critical insights into potential mechanisms of metastasis. These findings could enhance diagnostic accuracy and guide the development of targeted therapeutic strategies in rare metastatic cases of oncocytoma.